PERLINDUNGAN HAK CIPTA ATAS KARYA MUSIK DALAM PERJANJIAN KERJASAMA PENGELUARAN ALBUM MUSIK - NIM. A1012211041, DINDA ADRIANA PUTRI (Jurnal Fatwa Hukum, 2025)
ABSTRACT                         This study aims to analyze copyright protection for musicians in music album release cooperation agreements and analyze efforts to resolve copyright disputes over musical works in cooperation agreements in accordance with applicable law. In many practices, copyright license agreements for songs made with private deeds do not provide a guarantee of legal certainty for the protection of the economic rights of the parties, especially for songwriters or rights owners. At the time of making the agreement, the creator does not receive clear and complete information regarding the addition of cassettes, VCDs/DVDs sold by the label, the amount of royalties received for each additional sale of cassettes, VCDs/DVDs. In this study, the author uses a normative method, with a descriptive approach. The results of the study show that the regulations that have been regulated regarding copyright protection for musicians in music album release cooperation agreements are Government Regulation of the Republic of Indonesia Number 56 of 2021 concerning Management of Song and/or Music Copyright Royalties. Based on Article 8 of PP Number 56 of 2021 concerning Management of Song and/or Music Copyright Royalties, Royalty management is carried out by LMKN based on integrated data at the song and/or music data center. If a dispute has occurred, the creator or copyright holder or musician can determine the next step, whether the dispute is to be resolved peacefully through alternative dispute resolution such as mediation, negotiation, or conciliation through arbitration or through the courts.  Keywords: Protection, Copyright, Musical Works    ABSTRAK1  Penelitian ini bertujuan untuk menganalisis perlindungan hak cipta bagi musisi dalam perjanjian kerjasama pengeluaran album musik dan menganalisis upaya penyelesaian sengketa hak cipta atas karya musik dalam perjanjian kerjasama sesuai dengan hukum yang berlaku. Dalam banyak praktik perjanjian lisensi hak cipta atas lagu yang dibuat dengan akta di bawah tangan tidak memberikan jaminan kepastian hukum perlindungan hak ekonomi para pihak khususnya bagi pencipta lagu atau pemilik hak. Pencipta pada saat melakukan perjanjian tidak memperoleh informasi yang jelas dan lengkap mengenai penambahan kaset, VCD/DVD yang diperjual-belikan oleh label, jumlah royalti yang diterima untuk setiap penambahan penjualan kaset, VCD/DVD. Dalam penelitian ini Penulis menggunakan metode normatif., dengan pendekatan Deskriptif. Hasil penelitian menunjukkan bahwa Peraturan yang telah mengatur terkait dengan perlindungan hak cipta bagi musisi dalam perjanjian kerjasama pengeluaran album musik, yaitu Peraturan Pemerintah Republik Indonesia Nomor 56 Tahun 2021 tentang Pengelolaan Royalti Hak Cipta Lagu Dan/Atau Musik. Berdasarkan Pasal 8 PP Nomor 56 Tahun 2021 tentang Pengelolaan Royalti Hak Cipta Lagu Dan/Atau Musik, pengelolaan Royalti dilakukan oleh LMKN berdasarkan data terintegrasi pada pusat data lagu dan/atau musik. Apabila telah terjadi sengketa, maka pencipta atau pemegang hak cipta atau musisi dapat menentukan langkah berikutnya apakah sengketa tersebut ingin diselesaikan secara damai melalui alternatif penyelesaian sengketa seperti mediasi, negosiasi, atau konsiliasi melalui arbitrase atau melalui pengadilan.    Kata Kunci : Perlindungan, Hak Cipta, Karya Musik